Ranking and multicriteria decision making in optimization of raspberry convective drying processes. (5th February 2020) - Stamenković, Zoran; Radojčin, Milivoj; Pavkov, Ivan; Bikić, Siniša; Ponjičan, Ondrej; Bugarin, Rajko; Kovács, Sándor; Gere, Attila
Abstract: Serbia is one of the leading producers and exporters of raspberry in the world, and considering the short shelf life of raspberry, the processing, storage, and transport are some of the main issues to be addressed. A comparative experiment was conducted in order to find the suitable process parameters for convective drying that may be considered as the alternatives to freeze‐drying, which is a widely used preservation method for raspberry even though it is a costly and energy‐consuming method. Twelve convective drying regimens were applied with a combination of three influencing factors: air temperature (60°C, 70°C, and 80°C), air rate (0.5 and 1.5 m·s −1 ), and stage of raspberry (fresh and frozen). The final product, a dried raspberry, was assessed for chemical, physical, and mechanical properties and rehydration capacity. Deep ranking analysis by power eigenvectors (DRAPE) and sum of ranking differences (SRD) were used to uncover the differences and similarities between the applied drying methods. SRD showed that convective drying of fresh raspberries proved to be more similar to freeze‐dried raspberries than convective drying of frozen ones. Fresh samples dried at 60 °C air temperature and 1.5 m·s −1 air flow proved to be the most similar to the reference freeze‐drying method. This convective regimen gives samples with the lowest color change, shrinkage, and shape deformation. With the mechanical and chemical properties of these samples being observed, statistical Duncan's test show that there is no significant difference ( P < .05) in terms of hardness, shear force resistance, total phenolic, and total flavonoid preservation, compared with freeze‐dried samples. DRAPE gave similar results, but it added the variable importance in ranking as well, and total phenol reduction was defined as the most important variable. These results can help practitioners to develop cheaper and simpler drying methods that would replace the freeze‐drying but keep the same quality of the dried products. Abstract : The aim of this article is to find the suitable alternative to freeze‐drying of raspberry. Twelve convective drying regimens were applied with a combination of three influencing factors: air temperature (60°C, 70°C, and 80°C), air rate (0.5 and 1.5 m·s −1 ), and stage of raspberry (fresh and frozen). The sum of ranking differences (SRD) showed that convective drying of fresh raspberries at 60°C air temperature and 1.5 m·s −1 air flow proved to be the most similar to the reference freeze‐drying method.